2022
DOI: 10.1155/2022/8693479
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Phosphorus Solubilizing Purple Nonsulfur Bacteria Isolated from Acid Sulfate Soil in Improving Soil Property, Nutrient Uptake, and Yield of Pineapple (Ananas comosus L. Merrill) under Acidic Stress

Abstract: This study aimed to (i) evaluate purple nonsulfur bacteria (PNSB) strains possessing the highest phosphorus (P) solubilizing capacity in field and (ii) determine the efficacy of PNSB biofertilizers in improving soil quality, P uptake, growth, and yield of pineapple cultivated in acid sulfate soil (ASS). A field experiment was conducted in a completely randomized block design with two factors, including the first factor as P fertilizer levels (0, 50, 75, and 100% P) based on recommended fertilizer formula (RFF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The treatment supplied with bacteria had higher sugar content and water content than the treatment without bacteria. This was consistent with the study by Huu et al (2022). Moreover, in the treatment supplied with bacteria, values of L* and a* were higher than those in the treatment without bacteria, while b* values followed an opposite trend (Table 8).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The treatment supplied with bacteria had higher sugar content and water content than the treatment without bacteria. This was consistent with the study by Huu et al (2022). Moreover, in the treatment supplied with bacteria, values of L* and a* were higher than those in the treatment without bacteria, while b* values followed an opposite trend (Table 8).…”
Section: Discussionsupporting
confidence: 91%
“…Growth features were determined at harvesting when 20 plants were ran domly collected from each treatment and measured following the method of Huu et al (2022).…”
Section: Criteria Of Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…as biofertilizers in paddy felds have been reported to improve adverse efects of soil environments such as acidity, salinity, and toxicity [23][24][25][26][27][28][29] to enhance rice growth at diferent stages [25][26][27][28][30][31][32][33] and also rice productivity [29,33]. Additionally, the PNSB promoted the growth of various crops such as sweet herb Stevia rebaudiana [34], cucumber seedling [35,36], and pineapple [37]. Regarding previous studies, it has been suggested that the PNSB can be applied in both wetland and cultivated soils for annual crops; thereby, it would be worth to explore their roles for promoting growth and yield of sesame, particularly in dyked AS.…”
Section: Introductionmentioning
confidence: 99%